Implementation of the Use of Neuroscience-Based Arabic Learning Media on Students: A Case Study at Vocational High School Muhammadiyah 3 Yogyakarta - Jailani, Mohammad; Widodo, Hendro (Institut Agama Islam Negeri Curup, 2021)
This study aims to analyze neuroscience-based Arabic learning media at SMK Muhammadiyah 3 Yogyakarta. Implementation to students so they can memorize mufrodat, and practice muhadasah Arabic. The type of research used in this research is qualitative. The research subjects were teachers and students. Determination of research subjects is done by using purposive sampling. Data collection techniques were carried out using interview, observation, and documentation methods. The validity of this research data using triangulation. Data analysis used the Miles and Huberman model, namely by data reduction, data display, and conclusion drawing/verification data. The results of the study of neuroscience-based Arabic learning media that were applied in the classroom were identifying students with five (mufrodat). In addition, each student memorized five (mufrodat), and practice (muhadasah) with his classmates. directed by the teacher who responds to the student's brain. Learning media, in the form of videos in which it is more directed to the students' brains as the focus of learning Arabic. The Arabic learning video contains mufrodat material that is easy for students to memorize and practice. Facilitate students in memorizing mufrodat namely in maharah qiro'ah, kitabah, istima', and kalam. It means, students can read Arabic mufrodat or quwa'id correctly, students can write Arabic mufrodat or quwa'id with imla', students can listen to mufrodat correctly, and continued students can apply muhadasah fluently.